The Obligations and Rights to Obtain Compensation as a Result of the Space Objects Discovery - Sinar Aju Wulandari; Izzah Khalif Raihan Abidin; Zainal Abidin Achmad; Muhammad Ardy Prakoso (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2023)
Indonesia, as a nation where foreign space objects are discovered, holds theright to seek compensation, thereby addressing the country's claims toreinstate pre-damage conditions. Under international regulations, anycountry launching objects into outer space from its territory or launchfacilities assumes responsibility for damages incurred in other nations. Thisresearch employs a qualitative legal research methodology, employing bothstatutory and conceptual approaches. The statutory method scrutinizes lawspertinent to the identified legal concerns. The primary sources encompass the1967 Treaty on the Principles Governing State Activities in SpaceExploration and Utilization, including the Moon and Celestial Bodies, andIndonesia's Law Number 16 of 2002, Gazette Number 34 of 2002,Supplement State Gazette No. 4195. The study's findings highlight that the1968 Rescue Agreement broadened a state's obligations concerning astronautrescue, recovery, and repatriation, extending these responsibilities toencompass the return of space objects for exploration purposes. Therepatriation of foreign space objects mandates compensation for any damageresulting from the descent of celestial bodies. Therefore, Indonesia, underinternational legal frameworks, can pursue restitution for damages caused byspace objects from other nations, ensuring accountability and restoration ofaffected conditions.